Measuring Psychopathy via Small Sample of TriPM Items - Međedović, Janko; Damjanović, Andrijana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The Triarchic personality model of psychopathy represents one of the most prominent operationalizations of psychopathy. According to this model, psychopathy is characterized by Meanness, Boldness and Disinhibition. The instrument which measures these three dimensions is labeled as the Triarchic Personality Measure (TriPM). The goal of the present study was to construct a short self-report inventory by selecting a sample of TriPM items. Using theoretical rationale, we constructed the 15-item version of the scale by narrowing the content of the subscales. In Study 1 (N = 135), we showed correlations between the short and long versions of the scale, which were very high. Furthermore, we explored the correlations between the long scales, new measures of psychopathy, and HEXACO personality traits. This analysis revealed the similarities, but differences as well, between the two versions of TriPM. In Study 2 (N = 211) we explored the latent structure of the new measure which turned out to be excellent: all items loaded on their respective factors. Finally, we investigated the relations between new psychopathy scales, the Dark Tetrad traits, and substance use. The analysis revealed good convergent and divergent validity of the short TriPM scales. The research results showed adequate reliability (all αs ≥ .70) and validity for the short TriPM scales, thus recommending them for further use. However, researchers should be cautious in interpreting the results obtained from the short scales, since they are not equivalent to the long form of the instrument due to the narrowing of the original scales' content.